RENCANA REKLAMASI DAN REVEGETASI PADA LAHAN BEKAS TAMBANG BATUBARA DI PT. SURYA ANUGRAH SEJAHTERA PROVINSI JAMBI - Warniningsih; Asri Fridtriyanda; Dimas Pangestu (ReTII, 2022)
The coal mining system in Indonesia is generally carried out with an Open Mine. The basic characteristic of the open pit mining system is that it clears land and changes the landscape, so that it has the potential to have an impact on the environment, social and economy of the community. Based on environmental aspects, the existence of coal mining has the impact of changing landscapes, decreasing soil fertility, threats to biodiversity, decreasing water quality and decreasing air quality and environmental pollution. PT. Surya Anugerah Sejahtera (SAS) is a company engaged in coal mining. The coal mining concession area of ​​PT. SAS is located in Rantau Pandan Village, Rantau Pandan District, Bungo Regency, Jambi Province. The research method used is descriptive and comparative. Descriptive describes the reclamation plan that will be carried out and what is happening in the field. While the comparative compares the post-production reclamation plans that have been planned and those that occur in the field. The research parameters focus on the parameters of the reclamation activity plan consisting of land use and revegetation at PT. SAS. In Law Number 4 of 2009 concerning Mining and Coal, it has been regulated as a legal force in enforcing mining management efforts that must be environmentally friendly. Therefore PT. SAS is obligated to reclaim ex-mining land. The implementation of the reclamation plan that will be carried out by PT. Surya Anugrah Sejahtera (SAS) includes land surface regulation, spreading of root zone soil, erosion and sedimentation control and revegetation. This activity was carried out on an area of ​​10 ha. Structuring the land surface using an inward sloping bench terrace, spreading the root zone of 50,000 m3, erosion control and water management by making a trapezium-shaped drainage channel. Revegetation activities by planting legumes, pioneers, and inserts (local plants). The spacing used is 4x5 (pioneer) and 5x5 for beans.